Digital Strategy and Citizen Engagement in Digital Government: Evidence from Generation Z - chairunnisa amin; Ali; Sisno Riyoko (LP2M IAIN Palopo, 2026)
This study seeks to investigate the extent to which Digital Strategy and E-Government Service Quality influence Citizen Engagement within the context of local digital governance. It also explores the intermediary functions of Trust in E-Government and Government Reputation in shaping this relationship. Specifically, the research assesses not only the direct effects of the independent variables on citizen engagement but also the indirect effects that operate through trust and institutional reputation as mediating constructs. A quantitative survey approach was implemented. Data collection involved 150 Generation Z participants who are users of digital service platforms provided by the Jepara Regency government, recruited using purposive sampling. The data were examined using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, implemented through SmartPLS software. The empirical findings demonstrate that both Digital Strategy and the Quality of E-Government Services exert a positive and statistically significant effect on Citizen Engagement. Furthermore, Trust in E-Government and Government Reputation serve as mediating variables, transmitting the influence of the independent constructs to the level of citizen engagement. The implications underscore the necessity for local governments to move beyond technical digital improvements by strengthening trust and institutional credibility through enhanced transparency, reliable systems, and secure data governance. Further research should extend the study area and employ longitudinal methods to achieve a more comprehensive understanding of engagement patterns in the e-government environment.